Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1049/el.2016.3025
|View full text |Cite
|
Sign up to set email alerts
|

Lowpass filters approximation based on modified Jacobi polynomials

Abstract: he orthogonal Jacobi polynomials are not suitable for use as the characteristic function in the continuous-and discrete-time filter design, because they are not fulfilling the basic condition: to be pure odd or pure even. A simple modification of Jacobi polynomials, is performed to obtain a new filter approximating function is proposed. Magnitude frequency responses of obtained filters exhibit more general behaviour compared with that of classical Gegenbauer (ultraspherical) filters, due to one additional para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The magnitude‐squared characteristic function of a continuous‐time lowpass filter with m pairs of finite transmission zeros in the stopband can be written as An)(Ω2=i=1mnormalΩ2normalΩ0i22i=1mnormalΩ2normalΩ0i22+εp2λ2Jn(α,β)(Ω)21where λ=i=1m)(Ω0i21, Ω0i is i th zero position and Ω0i>1, n > 2 m denotes the filter degree, and εp is a passband edge ripple factor. The polynomial scriptJnfalse(α,βfalse)false(normalΩfalse)=1Cnfalse(α,βfalse)Pn(α,β)(Ω)+Pn(β,α)(Ω)is a modified Jacobi polynomials [1], generated by using the parity relation for Jacobi orthogonal polynomials Pnfalse(α,βfalse)false(normalΩ…”
Section: Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude‐squared characteristic function of a continuous‐time lowpass filter with m pairs of finite transmission zeros in the stopband can be written as An)(Ω2=i=1mnormalΩ2normalΩ0i22i=1mnormalΩ2normalΩ0i22+εp2λ2Jn(α,β)(Ω)21where λ=i=1m)(Ω0i21, Ω0i is i th zero position and Ω0i>1, n > 2 m denotes the filter degree, and εp is a passband edge ripple factor. The polynomial scriptJnfalse(α,βfalse)false(normalΩfalse)=1Cnfalse(α,βfalse)Pn(α,β)(Ω)+Pn(β,α)(Ω)is a modified Jacobi polynomials [1], generated by using the parity relation for Jacobi orthogonal polynomials Pnfalse(α,βfalse)false(normalΩ…”
Section: Approximationmentioning
confidence: 99%
“…Introduction: In the recently published paper [1], the authors have reported that the modified Jacobi polynomials can be used to construct a useful allpole lowpass filter functions. For the given lowpass filter degree, two parameters of the modified Jacobi polynomial can be used to a trade-off between passband magnitude response having ripples or being nearly monotonic, transition band width, or group delay deviation in the passband [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation